Prophylactic Oropharyngeal Surfactant Administration before Cord Clamping in Very Low Birth Weight Newborns - Silveira, Valentina; Machado, María Elena; Rodríguez-Rey, Marianela; Blasina, Fernanda; Díaz-Rossello, José Luis (Archives of Clinical and Biomedical Research, 2022)
Background: In the era of minimally invasive ventilatory strategies search, the prophylactic administration of surfactant with simple techniques, which do not require special skills, represents an innovative tool that, combined with delayed cord clamping, could reduce morbidity and mortality in premature babies. Methods: In this descriptive restrospective study, 27 cases of premature newborns who received prophylactic surfactant through the oropharyngeal route before the first breath and with intact circulation of the umbilical cord are reported. Results: After receiving the oropharyngeal surfactant 9 of 27 patients required endotracheal intubation in the first 24 hours. Only 2 of the 27 babies received 3 doses of surfactant by endotracheal way which corresponds to a total dose of 300 mg/kg. No major complications related to the oropharyngeal surfactant administration technique were registered. Seven patients did not require any other dose of surfactant after the administration of oropharyngeal surfactant. Bronchodysplasia was diagnosed in 2 of the 27 patients and the intraventricular hemorrhage was present in 3 patients. No patients with retinopathy of prematurity (ROP) were registered. Conclusions: The experience described with this surfactant administration technique was conducted in a setting prepared for the care of the neonate during the third stage of labor. After the successful de-implementation of immediate cord clamping in all deliveries, including preterm ones regardless of the mode of delivery, oropharyngeal surfactant administration is a non-invasive, safe, feasible, and reproducible technique that can be performed in low-complexity settings, with the potential to improve premature outcomes.